Health System Challenges in Managing Schistosomiasis Among Pregnant Women: A Qualitative Study from an Endemic Indonesian Highland - Lumeno, Indah Sari Purna; Saleh, Rahmawati (Jambura Medical and Health Science Journal, 2025)
Introduction: Schistosomiasis infection in pregnant women can lead to poor newborn health and reduced birth weight. The present study was conducted on an endemic area, while the risk of pregnant women being exposed to Schistosomiasis in the Napu Highlands is quite high. This study aims to describe the health care system related to Schistosomiasis in pregnant women within the Puskesmas Wuasa working area.Method: This study used a qualitative descriptive approach in the Puskesmas Wuasa working area in Poso Regency. The sample consisted of 11 key informants, including four pregnant women, three health workers, two Schistosomiasis laboratory workers, one head of the Puskesmas, and one official from a related agency. Data were collected through guided interviews.Results: Mass screening for Schistosomiasis occurs annually, but specific screening for pregnant women has not been implemented, despite their support for it. Pregnant women cannot take Praziquantel due to potential fetal risks and regulatory concerns. Positive tests lead to referrals by village midwives to Puskesmas. Additionally, Schistosomiasis insurance for pregnant women is readily accessible, often covered by government insurance, ensuring support for affected individuals.Conclusion: Current health services inadequately support pregnant women in Schistosomiasis -endemic areas, particularly in the Puskesmas Wuasa. The present study highlights the implementation gap in integrating schistosomiasis screening and treatment into antenatal care services within a specific endemic area. Ensuring the safety and regulation of praziquantel as the primary treatment is essential to optimize health services for this vulnerable group. Keywords: Delivery of health care, mass screening, praziquantel, pregnancy, schistosomiasis